Syiah Kuala University Tree Architecture - Vivera Ruselli Puspa (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
Research of “Syiah Kuala University Tree Architecture” conducted on March until April 2017. This research aims to know the tree architecture models. The research conducted in Syiah Kuala University and take 20 office unit to become research station, this sample is about 62,5% of the study area.  The method used in this study is survey with direct observation in the stastion. The analysis used  key determination tree architecture model and presentasion in picture and table. The result show there are 18 tree architecture model in the research station.